2021
DOI: 10.3390/math9182304
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of In Silico Fluid Simulations to Predict Thrombus Formation after Left Atrial Appendage Occlusion

Abstract: Atrial fibrillation (AF) is nowadays the most common human arrhythmia and it is considered a marker of an increased risk of embolic stroke. It is known that 99% of AF-related thrombi are generated in the left atrial appendage (LAA), an anatomical structure located within the left atrium (LA). Left atrial appendage occlusion (LAAO) has become a good alternative for nonvalvular AF patients with contraindications to anticoagulants. However, there is a non-negligible number of device-related thrombus (DRT) events,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 49 publications
2
47
0
Order By: Relevance
“…is study has focused on studying the influence of LA/ LAA morphology and in silico haemodynamics on thrombus formation before the implantation of a LAAO device, which can lead to a better patient selection and personalised therapy choice. However, the developed modelling pipeline to create haemodynamics simulations has also shown [17][18][19][20][21] to be useful in determining the formation of thrombus after the implantation of LAAO devices (i.e., device-related thrombus). Unfortunately, the required follow-up data to perform such verification were not available in the analysed patients in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…is study has focused on studying the influence of LA/ LAA morphology and in silico haemodynamics on thrombus formation before the implantation of a LAAO device, which can lead to a better patient selection and personalised therapy choice. However, the developed modelling pipeline to create haemodynamics simulations has also shown [17][18][19][20][21] to be useful in determining the formation of thrombus after the implantation of LAAO devices (i.e., device-related thrombus). Unfortunately, the required follow-up data to perform such verification were not available in the analysed patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) simulations with dynamic mesh movement of the mitral valve (MV) annulus ring were carried out by using ANSYS Fluent Solver 19.2 (Ansys, Inc., Pennsylvania, USA). In our study, we applied the boundary conditions (BCs) proposed by Mill et al [ 20 , 21 ]. They were defined as pressure inlet at the pulmonary veins (PVs) and as velocity outlet at the MV.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, we previously showed that fixed-wall simulations and moving-wall simulations produce comparable values of blood residence time inside LAAs of the same geometry [28]. Furthermore, while previous CFD analyses indicate that LAA residence time correlates inversely with the LAA ejection fraction [28], this correlation is imperfect and additional factors such as LA volume, LAA morphology, PV flow profiles, and the MV have been associated to vortical patterns and residence time inside the LAA [60, 61, 21]. Of note, LAA morphology is a well-known stroke risk factor in patients with AF [11].…”
Section: Discussionmentioning
confidence: 99%
“…Since Shettigar et al [49] reported blood residence time to examine the washout of artificial ventricles, this quantity has been used to study the risk of intracardiac thrombosis [12,28,50]. Patient-specific computational fluid dynamics (CFD) analyses are emerging as a tool to help assess LAA thrombosis risk in AF patients [23] and after LAA occluder device implantation [21]. However, previous investigations have considered constant fluid viscosity, neglecting the non-Newtonian rheology of blood at low shear rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation